The Impact of Digital Infrastructure on Creative Economy Growth in Indonesia - Kosasih Kosasih (International Journal of Artificial Intelligence Research, 2022)
Currently, creative economic growth is developing in Indonesia. One crucial element that needs to exist to be able to help the growth of this creative economy is the existence of developments in digital infrastructure. This research then looks at how digital infrastructure can impact the growth of the creative economy in Indonesia. This research will be carried out using a qualitative approach. The data used in this research comes from the results of previous research or studies that are still relevant to this research. The results of this study then found that the creative economy can grow and develop as a result of the development of digital infrastructure. Therefore, the government’s role in improving digital infrastructure is essential so creative economy actors can grow better.